Reduksi Sulfat oleh Bakteri Termofilik dari Air Panas Sarongsong Kota Tomohon - Jubhar C Mangimbulude (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Sulfate Reducing Bacteria (SRB) is very useful in the process of soil bioremediation as the former colliery land and contaminated heavy metal soil. The purpose of this research are to determine the content of sulfate in Sarongsong hot spring and determine the activity of SRB (anaerobic conditions) in three different stations. The sample in this study were drawn from Sarongsong hot spring Tomohon at three different stations, and are grouped in two groups: aerobic and anaerobic. This research was conducted in the laboratory of biological master CARC SWCU, Salatiga. The results of measurements performed after 7 days treatment. From three sampling stations Sarongsong hot spring; S1 S2, S3 were obtained that the sulfate content in the S3 is the largest 35 mg / L, followed by S2 11 mg / L and S1 3.5 mg / L. Sulfate reduction levels ranging from S1, S2, S3 conducted by SRB after 7 days treatment in a row is 185 mg/L; 191mg/L; and 197 mg/L. Station three (S3) has amount of sulfate reducing morethan S1 and S2. The results of this research provide information that Sulfate Reducing Bacteria is in Sarongsong hot spring Tomohon.